1995
DOI: 10.1136/thx.50.5.490
|View full text |Cite
|
Sign up to set email alerts
|

In vitro release of arachidonic acid metabolites, glutathione peroxidase, and oxygen-free radicals from platelets of asthmatic patients with and without aspirin intolerance.

Abstract: Background -An abnormal platelet release of oxygen-free radicals has been described in acetylsalicylic acid (aspirin)-induced asthma, a finding which might suggest the existence of an intrinsic, specific platelet abnormality of arachidonic acid metabolism in these patients. The objective of this study was to evaluate platelet arachidonic acid metabolism in asthmatic patients with or without intolerance to aspirin. Methods -Thirty subjects distributed into three groups were studied: group 1, 10 healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…Previous studies have shown that peripheral blood and platelet GSH-Px activities are reduced in aspirin-sensitive asthmatic patients [12][13][14][15] and some, but not all, studies have also demonstrated this in atopic asthmatic patients [15][16][17][18][19]. In our study of an Australian population, we showed that reduced GSH-Px activity was associated with reduced serum Se concentrations in atopic asthmatic patients, although the reasons for the reduced Se levels remain unclear [17].…”
Section: Introductionsupporting
confidence: 50%
“…Previous studies have shown that peripheral blood and platelet GSH-Px activities are reduced in aspirin-sensitive asthmatic patients [12][13][14][15] and some, but not all, studies have also demonstrated this in atopic asthmatic patients [15][16][17][18][19]. In our study of an Australian population, we showed that reduced GSH-Px activity was associated with reduced serum Se concentrations in atopic asthmatic patients, although the reasons for the reduced Se levels remain unclear [17].…”
Section: Introductionsupporting
confidence: 50%
“…This results in disturbances in calcium homoeostasis, which in their turn may cause the platelet activation, elevation of the Ca 2+ response to the minimal dose of melatonin in vitro in patients with AIA and striking deviations of platelet shape and ultrastructure found in patients with AIA [6,17]. A low platelet generation of melatonin in patients with AIA may also result in increased lipid peroxidation in platelets, which is consistent with published data on reduced platelet glutathione peroxidase activity and increased reactive oxygen species production in patients with AIA [18–21].…”
Section: Discussionsupporting
confidence: 80%
“…European Journal of Clinical Investigation Vol 41 783 platelet generation of melatonin in patients with AIA may also result in increased lipid peroxidation in platelets, which is consistent with published data on reduced platelet glutathione peroxidase activity and increased reactive oxygen species production in patients with AIA [18][19][20][21]. Thus, taking into account that platelets are one of the main extrapineal sources of melatonin in human organism, the defect of their membrane receptor organization resulting in lower production of melatonin in AIA provides another evidence of a major role of platelets in this form of bronchial asthma.…”
Section: (A) (B)supporting
confidence: 89%
“…Platelets play an important role in acute myocardial infarction [9], in inflammatory diseases such as rheumatoid arthritis [33] and in bronchial asthma [15,28]. According to the results of our study, platelets may also be involved in mechanisms of sciatica.…”
Section: Discussionsupporting
confidence: 53%